Academic Supervision: The Efforts to Improve Teachers' Abilities in Implementing Standards of Learning Process - Dermawati Dermawati (AL-ISHLAH: Jurnal Pendidikan, 2021)
The aim of the research is to provide information about the standards of the learning process, socialize the standards of the learning process and inform about the implementation of the standard implementation of the learning process for high school teachers in Bandar Lampung. This Research used Qualitative research method.  To collect data, the researcher uses observation sheets and documentation. The data analysis technique in this research is using qualitative data analysis. This school action research was designed in two cycles, which consists of planning, implementation, observation, and reflection stages. Data obtained from observations, documentation and portfolios were analyzed in the form of descriptions. The results shows there was a significant increase in each cycle. In some conditions the average value was 59.44 and included in enough category. In the first cycle the average value was 69.72 and was still included in the enough category, while in the first cycle secondly, the average acquisition value was 85.29 and it is still in the good category. From the explanation of the results of the assessment of the 4 aspects of the Implementation of the Learning Activity Process Standards, it shows that in the second cycle all results fall into the good criteria, so it can be concluded that the implementation of school action research is declared complete in the second cycle.